Effect of Static Annealing on Microstructure and Texture in Extruded Mg-Gd-Y-Zr Alloy. Issue 9 (September 2016) - Li, Li; Jie, Wu; Yuanzhi, Wu; Nam, Nguyen Dang
Abstract: The evolution of microstructure and texture for an extruded Mg-9Gd-4Y-0.6Zr alloy during static annealing was investigated. The grain growth, precipitation and texture modification were characterized by optical microscopy, scanning electron microscopy, transmission electron microscopy, XRD texture instrument and EBSD. The results show that the grain refinement at the initial stage of static annealing is caused by recrystallization. The intergranular deformation stimulates local precipitating, which in turn inhibits the recrystallization process. The texture analysis indicates that the hot extrusion produces the conventional basal fiber with {0001} // ED and the unusual prismatic fiber with c axis // ED. During static recrystallization, the grain nucleation weakens the prismatic fiber, while the grain growth strengthens it. A large number of plate phases precipitate at grain boundaries along with subgrain boundaries, which significantly inhibits the texture modification.